Fotografi di Hindia Belanda - Daniek Intan Pratiwi (Universitas Gadjah Mada, 2014)
This research analyses photography in the Netherlands Indies since the mid-19th century and its development until the early 20th century. The rise of photography in the Netherlands Indies as part of its modernization, is not merely the development of the arts, but photography was also used to explore the colonial territory of the colonial government. European photographers were sent to document archeological artefacts in various expeditions in several places in the archipelago.Photography also began to be commercialized. European, Chinese and even indigenous photographers arose with their photo studios. They have produced a natural and anthropological landscape of the Netherlands Indies, from Europeans and indigenous people living there. The commercialization of photography expanded with a variety of photo subjects, sold to other parts of the world in the form of albums, souvenirs or postcards. This answered the curiosity of the outside world on the Netherlands Indies as a colonial area.